Toxic Masculinity and İts İmpact on the Indian Culture - Sagar Jog (International Journal of Advanced Science and Technology, 2020)
This study focuses on the fact that how, in a country like India, the toxic masculinity is reinforced through the medium of advertisements and media and how assumptions are made about it. It also tells how the term "Toxic Masculinity" is tricky and if misunderstood can seem widely insulting. As the term requires careful contextualization and provokes strong reactions, the paper also tells how people usually avoid discussing it and how it is our responsibility not to hide from difficult topics, but to clarify them. The main aim of the research is to understand toxic masculinity, how it came into existence, how it affects society, what effects it has on an individual and how and why it is misunderstood and misinterpreted by the society. The study revolves around the factors which cause the phenomenon to be termed as toxic masculinity and why it is a popular topic among youth right now in the world! The study also tells how and why it is related or not related to feminism and how awareness and right information about it should be passed and shared.